Utilization of 3D Printing in Replacement of Basic Plastic Workpieces - Kristály , Álmos; Ficzere, Péter (International Journal of Engineering and Management Sciences, 2021)
In the experiment, a 3D printed cogwheel is made using the FDM technology to replace a broken part in a sewing machine. The aim of the project is to examine if a 3D model can be created and manufactured using only entry-level technical knowledge and tools. By the end of the article, it will be apparent that creating functioning plastic parts with a hobby 3D printer and basic CAD experience is very much possible.